Identifying East Java Trade Interest Through Paradiplomacy Initiatives - Analysis on Actors, Processes and Goals of Diplomacy - Fadhilah, Asshinaz Noor (Indonesian Journal of Social Development, 2024)
This research explores the paradiplomacy activities of the East Java Government's Department of Industry and Trade in improving international trade relations. Through initiatives such as business matching, trade fairs, and foreign trade missions, the government collaborates with trade attachés, ITPCs, and foreign trade representatives to promote Indonesian exports and attract foreign investment. By achieving strong trade performance, East Java has succeeded in attracting investment, increasing export value, and actively contributing to Indonesia's international trade. This study emphasizes the important role of local governments in advancing international trade for regional development and national interests. Through programs such as business matching, foreign trade missions, international exhibitions and market brief webinars. The East Java government uses paradiplomacy to strengthen international trade relations. This research underlines the role of subnational actors in increasing economic growth and Indonesia's foreign trade balance.